The Role of Integrin α6 (CD49f) in Stem Cells: More than a Conserved Biomarker - Krebsbach, Paul H; Villa-Diaz, Luis G (Stem cells and development, 2017)
Stem cells have the capacity for self-renewal and differentiation into specialized cells that form and repopulated all tissues and organs, from conception to adult life. Depending on their capacity for differentiation, stem cells are classified as totipotent (ie, zygote), pluripotent (ie, embryonic stem cells), multipotent (ie, neuronal stem cells, hematopoietic stem cells, epithelial stem cells, etc.), and unipotent (ie, spermatogonial stem cells). Adult or tissue-specific stem cells reside in specific niches located in, or nearby, their organ or tissue of origin. There, they have microenvironmental support to remain quiescent, to proliferate as undifferentiated cells (self-renewal), and to differentiate into progenitors or terminally differentiated cells that migrate from the niche to perform specialized functions. The presence of proteins at the cell surface is often used to identify, classify, and isolate stem cells. Among the diverse groups of cell surface proteins used for these purposes, integrin α6, also known as CD49f, may be the only biomarker commonly found in more than 30 different populations of stem cells, including some cancer stem cells. This broad expression among stem cell populations indicates that integrin α6 may play an important and conserved role in stem cell biology, which is reaffirmed by recent demonstrations of its role maintaining self-renewal of pluripotent stem cells and breast and glioblastoma cancer stem cells. Therefore, this review intends to highlight and synthesize new findings on the importance of integrin α6 in stem cell biology.